ANALISIS TINGKAT KEPUASAN PESERTA PENCAIRAN DANA JHT ATAS KUALITAS LAYANAN ONLINE DI BPJS KETENAGAKERJAAN CABANG RENGAT SELAMA PANDEMIC COVID-19 - Sari Puspita Wanda; Restuti Sri; Musfar Firli Tengku (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the analysis of the satisfaction level of JHT funddisbursement participants on the quality of online services at the BPJS ketenagakerjaanRengat branch office during the covid-19 pandemic. The population in this study includesall participants who have disbursed JHT funds and received online services at BPJS Employment Rengat branch, and the sample in the study amounted to 122 participants. Primary Data was collected by questionnaires as an instrument to prove the results of thestudy, to test the hypothesis in this study is using the analysis method Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). Sampling technique usingpurposive sampling method. Based on the results of the analysis of Importance Performance Analysis (IPA) indicators that are in quadrant I is no errors, features are clear,and as expected. indicators in quadrant II is timely, disbursement information, willing tobe contacted, being polite, providing contact, protecting data. Indicators in quadrant IIIis easily accessible, easy to register, quickly accessible, accuracy of Service, handlingcomplaints, online customer service, understanding problems and pleasant experiences.The indicator in quadrant IV is a quick interview, able to answer, according to sacrifice,satisfied overall. The results of the analysis of Customer Satisfaction Index (CSI) is in thecategory of very satisfied with the total value of 84.65% for online service quality variables and 84.79% for participant satisfaction variables.Keywords: Online Service Quality, Participant Satisfaction, Importance PerformanceAnalysis, Curtomer Index Satisfaction